A inserção do município de São Lourenço da Serra na Região Metropolitana de São Paulo: um estudo da geração de emprego e renda em uma área de proteção aos mananciais - Carrilho, Clécio José (2009)
The objective of this dissertation is to understand the path in the formation of the São Lourenço da Serra municipality, within the establishment of the Metropolitan Region of São Paulo (RMSP), administrative portion of São Paulo state, which binds the municipal. The research initially debates the historical constitution of São Lourenço da Serra, from the firmament of Indian villages, later as jesuistic environment responsible for Christian teaching and composition of the region. In view of this historical approach, it identifies local portions close to São Paulo, among them Embu, Itapecerica and Santo Amaro da Serra, which in holding religious character, it had important role in responding to the consolidation of the southwest portion RMSP, thus providing the dynamism that would make enable the emergence of important villages (towns), and then turned up politically emancipated areas. However, the Brazilian industrial growth ensures the formation of its territory and brings to the country's urban economic context, changes never assisted. The establishment of a region economically stronger would be constituted from a disorderly environment and with the incorporation of industry in economic activities in the country, would emerge distinct industrial clusters, blurring the São Paulo power. The RMSP decreases and aims other areas of expansion along the road warehouses; however, the population benefits from an insufficient purchasing power faced to the enrichment of the constituted metropolis, spread along the more remote portions of central cities. Indeed, emerge within the territory areas with low life quality, absent of the minimum sanitation conditions, employment and housing. As other areas of RMSP, São Lourenço da Serra is an example to be investigated, mainly because it was the last city emancipated that would belong to RMSP; in addition to present high growth rates when compared to the context of the metropolis and municipals with large economic potential. Thus, as the population rises, are exacerbate the social dilemmas, and part of these conflicts emerge of understanding of actors developers to generate income and employment. However, being inserted in the Water Protection Area (APM), among other specific laws to environmental preservation, conduct São Lourenço da Serra there are restrictions on the use and occupation of its soil, inhibiting the presence of certain economic activities generators of employment and income, promoters of the improvement of social dilemmas.Therefore, in addition to investigate the formation of the MRSP context, and the southwestern portion and the municipal, we establish in this research a report on the urban sprawl of São Lourenço da Serra, faced to of its inclusion within an area legally established, and therefore we define the issues conducted both by the government and society in regard to seek income and employment. Into the light of sustainability, we recognize the measures used and/or viable which can counterbalance the effective occupancy, growth and income for the maintenance and economic survival of the municipal